Optimization of dispersive liquid–liquid microextraction based on the solidification of floating organic droplets using an orthogonal array design and its application for the determination of fungicide concentrations in environmental water samples. Issue 15 (11th June 2014) - Yang, Xiaoling; Yang, Miyi; Hou, Bang; Li, Songqing; Zhang, Ying; Lu, Runhua; Zhang, Sanbing
<x xml:space="preserve">Abstract</x> A dispersive liquid–liquid microextraction method based on the solidification of floating organic droplets was developed as a simple and sensitive method for the simultaneous determination of the concentrations of multiple fungicides (triazolone, chlorothalonil, cyprodinil, and trifloxystrobin) in water by high‐performance liquid chromatography with variable‐wavelength detection. After an approach varying one factor at a time was used, an orthogonal array design [L25 (55)] was employed to optimize the method and to determine the interactions between the parameters. The significance of the effects of the different factors was determined using analysis of variance. The results indicated that the extraction solvent volume significantly affects the efficiency of the extraction. Under optimal conditions, the relative standard deviation (n = 5) varied from 2.3 to 5.5% at 0.1 μg/mL for each analyte. Low limits of detection were obtained and ranged from 0.02 to 0.2 ng/mL. In addition, the proposed method was applied to the analysis of fungicides in real water samples. The results show that the dispersive liquid–liquid microextraction based on the solidification of floating organic droplets is a potential method for detecting fungicides in environmental water samples, with recoveries of the target analytes ranging from 70.1 to 102.5%.